The Newborn's Reaction to Light as the Determinant of the Brain's Activation at Human Birth - Polese, Daniela; Riccio, Maria Letizia; Fagioli, Marcella; Mazzetta, Alessandro; Fagioli, Francesca; Parisi, Pasquale; Fagioli, Massimo (Frontiers in Integrative Neuroscience, 2022)
Developmental neuroscience research has not yet fully unveiled the dynamics involved in human birth. The trigger of the first breath, often assumed to be the marker of human life, has not been characterized nor has the process entailing brain modification and activation at birth been clarified yet. To date, few researchers only have investigated the impact of the extrauterine environment, with its strong stimuli, on birth. This ‘hypothesis and theory' article assumes the role of a specific stimulus activating the central nervous system (CNS) at human birth. This stimulus must have specific features though, such as novelty, efficacy, ubiquity, and immediacy. We propose light as a robust candidate for the CNS activation via the retina. Available data on fetal and neonatal neurodevelopment, in particular with reference to retinal light-responsive pathways, will be examined together with the GABA functional switch, and the subplate disappearance, which, at an experimental level, differentiate the neonatal brain from the fetal brain. In this study, we assume how a very rapid activation of retinal photoreceptors at birth initiates a sudden brain shift from the prenatal pattern of functions to the neonatal setup. Our assumption implies the presence of a photoreceptor capable of capturing and transducing light/photon stimulus, transforming it into an effective signal for the activation of new brain functions at birth. Opsin photoreception or, more specifically, melanopsin-dependent photoreception, which is provided by intrinsically photosensitive retinal ganglion cells (ipRGCs), is considered as a valid candidate. Although what is assumed herein cannot be verified in humans based on knowledge available so far, proposing an important and novel function can trigger a broad range of diversified research in different domains, from neurophysiology to neurology and psychiatry.